(untitled) (BIRDEM Medical Journal, 2021)
Background: Rheumatoid arthritis (RA) is a systemic inflammatory disease characterized by chronic and erosive polyarthritis causing irreversible joint disability. It is the most common persistent inflammatory arthritis, affecting from 0.5 to 1% of the general population worldwide. Antibodies to citrullinated proteins (anti-CCP antibody) have been described in patients with RA and these appear to be the most specific marker of the disease. Methods: This cross-sectional study was carried out at department of medicine, Sher-E-Bangla Medical College Hospital, Barisal Form July’ 2016 to December’ 2016. All rheumatoid arthritis patients attending at OPD and those got admitted under Medicine Dept, who was satisfying the inclusion and exclusion criteria were included consecutively and purposively in this study. Results: Total 70 cases were included; the mean age was found 46.57±13.10 years in anti-CCP antibody positive group and 44.19±11.21 years in anti-CCP antibody negative group. Female were predominant in both groups. Duration of disease was around 8 years in both groups. Mean ESR was 29.0±22.0 mm in anti-CCP antibody positive group and 12.25±10.6 mm in anti-CCP antibody negative group. Mean rheumatoid factor was 189.4±102.1 U/L in anti-CCP antibody positive group and 66.5±36.0 U/L in anti-CCP antibody negative group. Mean DAS 28 score was 4.6±1.4 and 3.6±1.3 in anti-CCP antibody positive and negative group respectively. The mean difference was statistically significant (p<0.05) between the groups. Patients in disease remission had lower anti-CCP antibody titer than those with low, moderate or high disease activity. Significantly positive correlation (r=0.596; p=0.001) between severity of rheumatoid arthritis and anti CCP antibody level was observed. Conclusion: In RA patients’ disease was more severe in anti-CCP antibody positive group and significantly positive correlation between anti-CCP antibody level with disease severity of RA was observed. BIRDEM Med J 2022; 12(1): 36-40